2015
DOI: 10.1002/asna.201512193
|View full text |Cite
|
Sign up to set email alerts
|

A review of East Asian reports of aurorae and comets circa AD 775

Abstract: Given that a strong 14C variation in AD 775 has recently been suggested to be due to the largest solar flare ever recorded in history, it is relevant to investigate whether celestial events observed around that time may have been aurorae, possibly even very strong aurorae, or otherwise related to the 14C variation (e.g. a suggested comet impact with Earth's atmosphere). We critically review several celestial observations from AD 757 to the end of the 770s, most of which were previously considered to be true, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 21 publications
2
50
0
Order By: Relevance
“…While the former event in 774/775 became widely discussed (e.g. Usoskin et al, 2013;Chapman et al, 2015;Hayakawa et al, 2016a), the latter event received far less attention and has only been discussed by Hayakawa et al (2015) and Stephenson (2015). The former, Hayakawa et al (2015), examined Chinese official history and found no relevant records between 988 and 996, but suggested a possibility of records in 992 in the Ulster Annals (Annala Uladh) and in German chronicles (Fritz, 1873) to be related with this event.…”
Section: Introduction: Carbon-14 Variations In 994mentioning
confidence: 99%
“…While the former event in 774/775 became widely discussed (e.g. Usoskin et al, 2013;Chapman et al, 2015;Hayakawa et al, 2016a), the latter event received far less attention and has only been discussed by Hayakawa et al (2015) and Stephenson (2015). The former, Hayakawa et al (2015), examined Chinese official history and found no relevant records between 988 and 996, but suggested a possibility of records in 992 in the Ulster Annals (Annala Uladh) and in German chronicles (Fritz, 1873) to be related with this event.…”
Section: Introduction: Carbon-14 Variations In 994mentioning
confidence: 99%
“…One could imagine that Marius and his visitor would have at least tried to observe spots together during the visit. If the weather was too overcast on that or those day(s), then he would instead have 13 In occidental records, words like fire or burning indicate both red colour and some (apparent) motion for aurorae, flame(s) do(es) not necessarily indicate red colour; in oriental reports, the phrases like fire and like flame(s) do not mean red colour nor motion; most oriental reports are written by astronomers, they mention explicitly colour and changes, see and Chapman et al (2015) for more discussion about aurora criteria. For the possible aurora on 1611 Nov 29, we know only that Lee et al (2004) describe them as red, but we cannot exclude that the original text reports only flames, i.e.…”
mentioning
confidence: 99%
“…What is reported as a white vapour penetrating the Moon may well be some halo effect around the Moon, which is quite possible 2 days before the full moon. For a discussion of the aurora sightings around the full moon, see Chapman, Neuhäuser, Neuhäuser, and Csikszentmihalyi ().…”
Section: Discussion Of the Early Observationmentioning
confidence: 99%